Content identification for the development of a nutrition resource kit for malnourished and at-risk elderly: a review - Noor Azam, Iman Nabihah; Hamirudin, Aliza Haslinda; Harith, Sakinah; Md Aris, Mohd Aznan; Abd. Aziz, Karimah Hanim; Sheikh Hishamuddin, Siti Nur Amirah; A Rashid, Nurul Syaireen (Nutrition Society of Malaysia, 2021)
Introduction: Elderly population is more likely to suffer from malnutrition, thereby requiring appropriate nutrition education as part of nutrition intervention to overcome this issue. This review aims to identify content suitable for developing a nutrition resource kit that provides nutritional guidance to combat malnutrition among malnourished and at-risk elderly in health clinics setting, particularly in Malaysia. Methods: A literature search was conducted up to 15th December 2019 in four databases: PubMed, Scopus, COCHRANE, and ProQuest Health & Medical Collection. Potential literature on nutrition education, suitable dietary guidelines and existing educational materials for elderly in the community, in English and Malay languages, were searched to identify suitable content for the nutrition resource kit. All relevant documents were included based on inclusion and exclusion criteria. Data were extracted and analysed according to the PRISMA-ScR guidelines. Results: A total of 27 documents consisting of articles, printed materials and guidelines were included for analysis. Suitable content included information related to malnutrition such as definition, signs and symptoms, cause-consequences, and nutrition management, which included food plate, serving size, menu suggestion, examples of recipes, tips to increase energy and protein intakes through food or drink, texture modification, a guide to using oral nutritional supplements, tips for maintaining nutrient content in food and drink, tips to encourage to eat, and oral health. Conclusion: A nutrition resource kit tailored for malnourished and at-risk elderly would be a beneficial nutrition intervention. There is a need to incorporate these information in the development of a nutrition resource kit to improve their dietary intake.